RESISTANCE OF ANOPHELES STEPHENSI LISTON TO MALATHION IN THE PROVICE OF FARS, SOUTHERN IRAN - N.Eshghy; H. Ladoni E. Javadian (Tehran University of Medical Sciences, 1985)
Anopheles Stephensi is an important malaria vector in southern Iran. This species developed resistance to DDT in 1975 and subsequently to dieldrin in 1960. Since 1968 this species has been under pressure of malathin house sprayin. 50% w.d.p. , 2g/m2, 1-2 rounds per year. Susceptibility tests carried out with malathion impregnated papers during 1979 showed that An.stephensi has acquired resistant to malathion too. With regard to the 0.1% propoxur, a study was carried out to obtain base-line data in the localities under routine observations and also the discriminating dosage that could kill 100% of An.stephensi. The objective of the present paper is to summarize and discuss briefly the field investigations concerning insecticide resistance in An.stephensi.